1976
DOI: 10.1079/bjn19760028
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the zinc status of pigs and the occurrence of copper- and Zn-binding proteins in liver

Abstract: 1. A study has been made by gel filtration techniques of the soluble copper- and zinc-binding proteins in livers from pigs of different Zn status. 2. The distribution of both Cu and Zn between the three fractions isolated was greatly influenced by the Zn status of the animal. In livers from pigs given a Zn-supplemented diet the proportion of either Cu or Zn found in the fraction with a molecular weight of about 12 000 (fraction 3) was a direct function of the total liver concentration of the metal. In livers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Although Cu is a poor inducer of MT synthesis, it has been demonstrated in many animals species that Cu can bind to hepatic MT by competing with Zn for the binding sites: this is because Cu has a higher affinity for MT than Zn, and thus can compete with and displace Zn from the MT even after Zn has induced its synthesis (Bremner and Beattie, 1995;Bremner, 1998). However, a previous study found no evidence of similar competition between Cu and Zn for MT binding sites in porcine liver (Bremner, 1976), possibly due to the large MT-binding capacity in this species, which could be of some significance with regard to the greater resistance of these animals to copper toxicosis. Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Although Cu is a poor inducer of MT synthesis, it has been demonstrated in many animals species that Cu can bind to hepatic MT by competing with Zn for the binding sites: this is because Cu has a higher affinity for MT than Zn, and thus can compete with and displace Zn from the MT even after Zn has induced its synthesis (Bremner and Beattie, 1995;Bremner, 1998). However, a previous study found no evidence of similar competition between Cu and Zn for MT binding sites in porcine liver (Bremner, 1976), possibly due to the large MT-binding capacity in this species, which could be of some significance with regard to the greater resistance of these animals to copper toxicosis. Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Intestinal absorption of appropriate amounts of zinc which perceptibly change the zinc status of the animal induces the synthe sis of thionein, the apoprotein of metallo thionein in the liver [7], The presence of thionein may hasten the uptake of absorbed zinc into the liver cell from the plasma, resulting in a short-term hypozincemia. Metallothionein-bound zinc has been found only in livers of pigs fed a Zn-supplemented diet [6], In Zn-depleted rats it could recently be demonstrated that plasma zinc increased by 3 h after feeding a Zn-supplemented diet, and that the following decrease coincided with the synthesis of hepatic metallothionein [31].…”
Section: Discussionmentioning
confidence: 99%
“…Nederbragt (12) found that, in plasma of rats, Mo promoted the appearance of a Cu fraction firmly bound to protein, uncommon in non-Mo-fed rats. (3,4,6), pig (2) and cattle (3,4). The distribution of copper and zinc between the proteins was variable and dependent on both the Cu and the Zn status of the animals.…”
Section: Introductionmentioning
confidence: 99%